RELIGIUSITAS, TAX KNOWLEDGE DAN E-SYSTEM TAX ADMINISTRATION DALAM MENJELASKAN KEPATUHAN WAJIB PAJAK DALAM PELAPORAN SPT TAHUNAN - Sifaur Robbyah, Aizzah; Afendi, Arif (STIE PENA, 2024)
This study aims to examine the influence of religiosity, tax knowledge, and e-system tax administration on the level of compliance of individual taxpayers in reporting Annual Tax Returns at KPP Pratama Cibitung, West Java. The sample method used is incidental sampling. The number of respondents used as a sample was 100 respondents who were individual taxpayers and employees at KPP Pratama Cibitung. The analysis and data processing process in this study uses multiple linear regression analysis. The results of this study show that the religiosity variable, tax knowledge variable, and e-system tax administration variable have a positive and significant effect on taxpayer compliance.